Alamesra Futsal Center - Mohd Yusof, Mohd Shazwan; Banati, Nissy Felicia; Ajat, Nor Suriane; Azmie, Nur Aisah; Jamil, Shahriezam (2011)
Government of Malaysia had now encouraged sport and making it compulsory in the requirement of qualification in order to get a better job, in government sector and also private sector. As a Malaysian, it is became a huge opportunity to support the effort of government to ensure the well being of our own country. Thus for the reason, we decided to make up with a new idea to built an indoor soccer court. We are starting our own business as partners and all of us decided to call our business as Alamesra Futsal Centre (AFC). Our main activity is providing indoor soccer at the same time providing places to play pool with unique packaging, great treat and affordable for everyone. Other than that we provide facilities such as Wi-Fi and rent shoes and other stuff for playing indoor soccer such as jersey for a team, beep, and Shin guard and so on. After make a meeting with the entire business partner we had decided to build the indoor soccer court in the area of Sepanggar, which located at the Alamesra. The reason why we choose this location is because it was a strategic location to start a business as it easy to reach by people from all over the place. This location is also well known due to the location just in the centre of massive development. Furthermore, the decided location nearby with One Borneo so the possibility for our premises to be known is very huge. For more Alamesra is located nearby with the college or university such as UiTM Sepanggar, Politechnic, UMS and other college that become our target market. We forecast there are huge potential of Alamesra to growth in the future.